Identifikasi Arsitektur Kolonial Terhadap Bangunan T. Bustamam, Meuligoe Bireuen dan Rumoh Ampon Loethan - M Farhan; A Dafrina; Y Novianti (Jurnal MESIL (Mesin Elektro Sipil), 2024)
Indonesia has a diverse culture and abundant natural resources, making it one of the richest countries. This is what encouraged the Dutch to enter Indonesia. Indonesian colonial architecture is a unique cultural phenomenon due to the cultural mix between immigrants and the diversity of Indonesian culture. The process of acculturation and assimilation with Indonesian culture and environment has transformed this architecture into something new. Many Dutch colonial heritages in Bireuen still stand strong today, including the T. Bustamam, Meuligoe Bireuen and Rumoh Ampon Loethan buildings. Colonial architecture can be seen from the characteristics of the building. This research is a qualitative research approach through observation, interviews and documentation. This research was conducted to find out the form of influence of the influx of Dutch culture, especially in the field of architecture, through the identification of Colonial architecture in the T. Bustamam, Meuligoe Bireuen and Rumoh Ampon Loethan buildings.